Halal Tourism: The Existence of One Village One Product-Based Cultural Tourism Development in Banyumas Regency - Sochimin (Wealth: Journal of Islamic Banking and Finance, 2022)
This study aims to identify the prospects and existence of cultural tourism in Banyumas Regency with the concept of One Village One Product (OVOP) halal tourism. This is done because the halal concept has now become a lifestyle for most Indonesian people. This type of research is library research, which is defined as the acquisition of data and information from library sources, such as books, studies, journals, and other reading materials relevant to the subject of this research. The study was conducted in Banyumas Regency and explained the concept of “one village, one product”. The survey results show that Banyumas Regency has enormous tourism potential, and there are opportunities to integrate the concept of OVOP-based halal tourism into Banyumas tourism, especially the development of cultural tourism, because Banyumas is known as a national hero city. Regions must have and develop their own unique identity that other regions do not have. This difference will increase the number of tourists visiting. This concept can be an example or role model for other regions in the management and development of halal tourism in the future.